2021
DOI: 10.1057/s41288-020-00197-0
|View full text |Cite
|
Sign up to set email alerts
|

Directors and officers liability insurance and default risk

Abstract: This paper investigates the effects of directors and officers (D&O) liability insurance on default risk. Using unique panel data of non-financial listed firms in Taiwan from 2010 to 2017, the empirical results indicate that D&O insurance exerts a significantly positive influence on firms' expected default frequency (EDF), controlling for the endogeneity of D&O insurance coverage and fixed effects. Further analyses reveal that such an effect exists particularly among firms with a high D&O insurance coverage rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…This indicates a clear positive correlation between the purchase of D&O liability insurance (Doins) and the level of corporate risk-taking (Risk), meaning that purchasing D&O liability insurance helps to enhance a company's ability to bear risk, confirming Hypothesis H2. This finding is consistent with the conclusions of studies by Boyer & Tennyson (2015), Kim (2016), Hwang & Kim (2018), Wang et al (2020), and others.…”
Section: Mediation Effect Testsupporting
confidence: 94%
See 1 more Smart Citation
“…This indicates a clear positive correlation between the purchase of D&O liability insurance (Doins) and the level of corporate risk-taking (Risk), meaning that purchasing D&O liability insurance helps to enhance a company's ability to bear risk, confirming Hypothesis H2. This finding is consistent with the conclusions of studies by Boyer & Tennyson (2015), Kim (2016), Hwang & Kim (2018), Wang et al (2020), and others.…”
Section: Mediation Effect Testsupporting
confidence: 94%
“…Priest (1987) considered D&O liability insurance a good incentive for attracting excellent senior management talent, promoting positive company development. D&O liability insurance primarily enhances a company's risk-taking capacity through the "incentive effect" (Boyer & Tennyson, 2015;Kim, 2016), with risk-taking behavior and company value increase being significant for companies with greater growth opportunities (Hwang & Kim, 2018). Wang et al (2020) also believe that the incentive role of D&O liability insurance increases the management and company's tolerance for risk, enhancing governance effects and providing a clear impetus for corporate innovation.…”
Section: Management Incentive Effectmentioning
confidence: 99%
“…In addition to the firm’s risk environment, opportunities for growth are also expected to moderate the CSR–risk relationship. Recent studies in the risk management and insurance field have shown that high-growth firms face greater litigation risk in general, and greater D&O litigation risk in particular ( Du et al, 2020 ; Huang, 2022 ; Hwang & Kim, 2018 ). When a firm faces a security class-action lawsuit, directors and officers could potentially suffer from both financial and reputational losses ( Brochet & Srinivasan, 2014 ; Fich & Shivdasani, 2007 ; McTier & Wald, 2011 ), especially when the lawsuits are combined with actions from the government or industry agencies ( Helland, 2006 ).…”
Section: Empirical Literature Review and Hypothesis Developmentmentioning
confidence: 99%